Affect, alienation, and awkwardness: Why I sing to my students (a non-representational consideration). (February 2020) - Lewkowich, David
Highlights: Recognizes the body as a site of multimodal formation. Discusses the affect-laden situation of embodied composition in singing. Theorizes the performatively unexpected nature of singing in the classroom. Considers how singing may encourage collective experiences of defamiliarization. Theorizes singing in relation to the commitments of non-representational work.